2020
DOI: 10.1186/s12883-020-01872-4
|View full text |Cite
|
Sign up to set email alerts
|

KIF1A-related autosomal dominant spastic paraplegias (SPG30) in Russian families

Abstract: Background: Spastic paraplegia type 30 (SPG30) caused by KIF1A mutations was first reported in 2011 and was initially considered a very rare autosomal recessive (AR) form. In the last years, thanks to the development of massive parallel sequencing, SPG30 proved to be a rather common autosomal dominant (AD) form of familial or sporadic spastic paraplegia (SPG),, with a wide range of phenotypes: pure and complicated. The aim of our study is to detect AD SPG30 cases and to examine their molecular and clinical cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 38 publications
(83 reference statements)
0
2
0
2
Order By: Relevance
“…c.296C>T(p.T99M)是 KIF1A 热点突变,此前已有至少9例病例报道 [ 16 21 - 25 ] 。与本研究纳入的2例患儿类似,受累患者往往表型较为严重,存在中度到极重度不等的智力障碍和发育迟缓,大多丧失行走能力,出现痉挛或癫痫症状,多有眼部异常如视神经病变或萎缩,部分患者还可合并小头畸形。Thr99位于KIF1A运动结构域高度保守的p环共识ATP结合位点,在原代大鼠海马神经元中的实验显示,与野生型比较,T99M变异的KIF1A远端定位大大减少,整个细胞体和近端神经元的聚集增加 [ 22 ] 。R254Q变异已在2例病例中报道,分别为一例8岁男童(5岁起病) [ 26 ] 和一例5岁女童(2~3岁起病) [ 27 ] 。与本研究中携带R254Q变异的患儿类似,3例患儿均症状较轻,尽管存在步态障碍,但能够独立行走,病程进展较慢。L249V虽为本研究首次发现,但已有L249Q [ 21 ] 和L249P [ 28 ] 的病例报道,表型均比本研究中携带L249V变异的患儿严重,除了共同存在的运动发育迟缓和痉挛,2例已报道患儿还合并中等程度的智力障碍。此外,携带L249Q变异的患儿行走需要辅助,伴有视神经萎缩;携带L249P变异的患儿存在痉挛性截瘫、全身性癫痫发作、眼震颤,兴趣有限、沟通不畅,并且小脑萎缩。已报道的c.798+1G>T患儿存在中度痉挛步态 [ 27 ] ,但与本研究中c.798+1G>A变异患儿仅有运动发育迟缓和步态异常表现明显不同的是,前者还存在兴趣有限、社交困难等类似自闭症谱系障碍的特征。可见 KIF1A 基因相同位置的不同变异可造成表型和严重程度的不同。…”
Section: 讨论unclassified
See 1 more Smart Citation
“…c.296C>T(p.T99M)是 KIF1A 热点突变,此前已有至少9例病例报道 [ 16 21 - 25 ] 。与本研究纳入的2例患儿类似,受累患者往往表型较为严重,存在中度到极重度不等的智力障碍和发育迟缓,大多丧失行走能力,出现痉挛或癫痫症状,多有眼部异常如视神经病变或萎缩,部分患者还可合并小头畸形。Thr99位于KIF1A运动结构域高度保守的p环共识ATP结合位点,在原代大鼠海马神经元中的实验显示,与野生型比较,T99M变异的KIF1A远端定位大大减少,整个细胞体和近端神经元的聚集增加 [ 22 ] 。R254Q变异已在2例病例中报道,分别为一例8岁男童(5岁起病) [ 26 ] 和一例5岁女童(2~3岁起病) [ 27 ] 。与本研究中携带R254Q变异的患儿类似,3例患儿均症状较轻,尽管存在步态障碍,但能够独立行走,病程进展较慢。L249V虽为本研究首次发现,但已有L249Q [ 21 ] 和L249P [ 28 ] 的病例报道,表型均比本研究中携带L249V变异的患儿严重,除了共同存在的运动发育迟缓和痉挛,2例已报道患儿还合并中等程度的智力障碍。此外,携带L249Q变异的患儿行走需要辅助,伴有视神经萎缩;携带L249P变异的患儿存在痉挛性截瘫、全身性癫痫发作、眼震颤,兴趣有限、沟通不畅,并且小脑萎缩。已报道的c.798+1G>T患儿存在中度痉挛步态 [ 27 ] ,但与本研究中c.798+1G>A变异患儿仅有运动发育迟缓和步态异常表现明显不同的是,前者还存在兴趣有限、社交困难等类似自闭症谱系障碍的特征。可见 KIF1A 基因相同位置的不同变异可造成表型和严重程度的不同。…”
Section: 讨论unclassified
“…目前已鉴定到的 KIF1A 变异主要集中在运动结构域,且大部分源自散发病例;目前已报道的200余例 KIF1A 基因变异患者中 [ 2 15 - 16 27 29 - 30 ] ,近70%为患儿自发新生突变。除上述少数变异位点外,大部分 KIF1A 基因变异尚未建立显著的基因型-临床表型关联,仍需积累更多病例数据观察。最近有假说提出了一种变异特异性的剂量效应:一些变异可能仅涉及远端轴突顺行运输的轻微损伤,导致较轻微的表型;而另一些变异可能损害近端轴突及其他神经元群体,导致严重的表型;少数已报道的功能丧失型变异会造成KIF1A蛋白水平降低而导致运输减少 [ 3 ] 。然而即使是同一变异的患者也存在临床异质性,或许需要考虑其他驱动蛋白的补偿机制以及其他未知的遗传或环境因素。…”
Section: 讨论unclassified
“…A 2020 literature review of 86 SPG30 cases did not reveal parkinsonism as a feature in any reported cases. 9 It is possible that the patient developed idiopathic Parkinson's disease at Kinesin-like protein KIF1A is a microtubule motor protein, or kinesin, involved in the antegrade transport of vesicles required for pre-and post-synaptic assembly, autophagy, and neuron survival. These vesicles transport membrane proteins such as vesicular monoamine transporter-2 (VMAT), which in turn acts to concentrate monoamines into presynaptic vesicles.…”
mentioning
confidence: 99%
“…A 2020 literature review of 86 SPG30 cases did not reveal parkinsonism as a feature in any reported cases. 9 It is possible that the patient developed idiopathic Parkinson's disease at age 53 that caused decompensation of her longstanding SPG30, given the levodopa response, motor fluctuations, visual hallucinations, and rapid progression after parkinsonism.…”
mentioning
confidence: 99%